Obraz filmowy jako dzieło sztuki - Hendrykowski, Marek (Wydawnictwo Naukowe UAM, 2003)
The language of film art, or the artistic language of cinematography, is not a separate kind of language of moving images. It is only its specific kind whose basic function consists in looking for the ever newer layers of cinematographic expression in film, TV spectacle, video-art, "light, music and sound" performance and the like. The work of art of the moving image appears to be an utterance constructed in a peculiar manner. Signs used in it become signs of signs, images shown are images of images. Such a work, due to the specificity of its formation is characterised by information capability which is considerably higher than that of an ordinary non-artistic communication. The model of reality contained in it is richer, which results from a much deeper combination of elements co-creating its structure and its characteristic expression. Many meanings as a semantic principle and as an element of the art of moving images which is of main importance, distinguishes the work of this art from all the other kinds of cinematographic communications, which generally avoid the effect of many meanings.
Film image as a work of art